Effect of Different Stocking Densities on Growth and Survival Rates of Sea Cucumber Holothuria scabra Seedlings - Serang, Abdul Malik; Tua Rahantoknam, Santi Penina; Tomatala, Pitjont (Aquacultura Indonesiana, 2016)
As sea cucumber, Holothuria scabra is one of the fishery commodities which have high economic value, this species now is under overexploited. Sea cucumber aquaculture should be developed urgently. This research was conducted to evaluate the effects of stocking densities on the growth and survival rates of sea cucumber. This research was carried out  by using pen culture with 5 – 9 cm in length or 30 – 50 g of seedlings. The sea cucumber was reared with stocking densities of 15 (treatment A), 20 (treatment B) and 25 individual/m2 (treatment C) in triplicates. The observation of growth and survival rates were done every two week. The water quality was measured every three day. The result indicated that the growth and survival rates was higher in treatment A than treatments B and C.